Enhancing the flow characteristics in a branching channel based on a two-dimensional depth-averaged flow model - Ali, Hydar Lafta; Yusuf, Badronnisa; Mohammed, Thamer Ahmed; Shimizu, Yasuyuki; Ab Razak, Mohd Shahrizal; Mohamed Rehan, Balqis (MDPI, 2019)
Natural rivers have many branching junctions. The flow in branching junctions is complex, owing to significant changes associated with flow dynamics and sediment transport that result in erosion and deposition problems. A branching channel of the Tigris River in Missan, Iraq, was selected for investigation of the scouring and deposition zones. A two-dimensional (2D) numerical model was used to simulate the hydro-morphodynamics in the branching channel, where hypothetical vanes as control structures were included at the junction to control the scouring and deposition zones. The simulation results suggest the most effective location, dimension, and angle of the introduced vanes. For the studied junction, controlling morphological features was achieved by introducing a single vane with an inclination angle of 90° on the flow direction of the Tigris River. The most effective location of the introduced vane was the location that caused considerable enhancement in the flow depth and velocity distribution.